Traumatic ulcerative granuloma with stromal eosinophilia - Aashka Sethi; Akanksha Banga; Ritika Raja; Reema Raina (Wolters Kluwer Medknow Publications, 2020)
Oral ulcers constitute one of the most common chief complaints of patients attending any dental practice. The cause of oral mucosal ulceration is generally attributed to acute or chronic trauma from local factors. However, oral lesions may be the initial manifestation of many systemic conditions. Moreover, a group of oral ulcerative lesions have been reported to exhibit vast numbers of eosinophils and known as Traumatic Ulcerative Granuloma with Stromal Eosinophilia (TUGSE). We present two cases of oral ulcers which on microscopic examination exhibited numerous eosinophils from ulcerated epithelium to deep into the submucosa and an exuberant lymphoid proliferation. CD15 immunohistochemical marker was used in these cases to ease the identification of the eosinophils. We also highlight the differential diagnosis of TUGSE that may manifest as oral lesions, as an important diagnostic guide for clinicians in contemporary practice.